Smart biomedical device to predict lung diseases, COVID-19 and diabetes by using machine learning algorithms - Hossain, Ashraful; Pranto, Shahidul Islam; Alif, MD.Nur-e-Sultan; Fahim, Mohammad Moontasir (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.